#Globalhealth Twitter Conversations on #Malaria, #HIV, #TB, #NCDS, and #NTDS: a Cross-Sectional Analysis - Isaac Chun-Hai Fung; Ashley M. Jackson; Jennifer O. Ahweyevu; Jordan H. Grizzle; Jingjing Yin; Zion Tsz Ho Tse; Hai Liang; Juliet N. Sekandi; King-Wa Fu (Ubiquity Press, 2017)
Background Advocates use the hashtag #GlobalHealth on Twitter to draw users' attention to prominent themes on global health, to harness their support, and to advocate for change. Objectives We aimed to describe #GlobalHealth tweets pertinent to given major health issues. Methods Tweets containing the hashtag #GlobalHealth (N = 157,951) from January 1, 2014, to April 30, 2015, were purchased from GNIP Inc. We extracted 5 subcorpora of tweets, each with 1 of 5 co-occurring disease-specific hashtags (#Malaria, #HIV, #TB, #NCDS, and #NTDS) for further analysis. Unsupervised machine learning was applied to each subcorpus to categorize the tweets by their underlying topics and obtain the representative tweets of each topic. The topics were grouped into 1 of 4 themes (advocacy; epidemiological information; prevention, control, and treatment; societal impact) or miscellaneous. Manual categorization of most frequent users was performed. Time zones of users were analyzed. Findings In the entire #GlobalHealth corpus (N = 157,951), there were 40,266 unique users, 85,168 retweets, and 13,107 unique co-occurring hashtags. Of the 13,087 tweets across the 5 subcorpora with co-occurring hashtag #malaria (n = 3640), #HIV (n = 3557), #NCDS (noncommunicable diseases; n = 2373), #TB (tuberculosis; n = 1781), and #NTDS (neglected tropical diseases; n = 1736), the most prevalent theme was prevention, control, and treatment (4339, 33.16%), followed by advocacy (3706, 28.32%), epidemiological information (1803, 13.78%), and societal impact (1617, 12.36%). Among the top 10 users who tweeted the highest number of tweets in the #GlobalHealth corpus, 5 were individual professionals, 3 were news media, and 2 were organizations advocating for global health. The most common users' time zone was Eastern Time (United States and Canada). Conclusions This study highlighted the specific #GlobalHealth Twitter conversations pertinent to malaria, HIV, tuberculosis, noncommunicable diseases, and neglected tropical diseases. These conversations reflect the priorities of advocates, funders, policymakers, and practitioners of global health on these high-burden diseases as they presented their views and information on Twitter to their followers.